The molecular characterisation of the recA locus in the opportunistic pathogen Bacteroides fragilis - Nicholson, Samantha Anne (Department of Molecular and Cell Biology, 2014)
Bacteroides fragilis is a human gut commensal and an opportunistic pathogen causing anaerobic abscesses and bacteraemias which are treated with the drug, metronidazole, a DNA damaging agent. The RecA protein is thought to be involved in the repair of metronidazole damage as well as damage caused by oxidative stress. The ability to survive oxygen stress is a strong indicator in an anaerobic bacterium of pathogenic potential and bacterial persistence in the oxygen rich peritoneal cavity. The aim of this thesis was to characterise the B. fragilis recA gene cluster with respect to its genomic context and the transcriptional regulation of the genes in response to metronidazole and oxygen stress. The possible functional roles of the proteins encoded by these genes in protection against these processes would also be evaluated. The functional characterisation of the RecA protein from B. fragilis showed that it was important for survival after exposure to nitrogen (metronidazole) and oxygen (hydrogen peroxide) radicals. RecA was shown to be important for the maintanence of genomic integrity even under normal growth conditions, and overexpression of this protein was shown to be important for increased survival after exposure to metronidazole. RT-PCR of B. fragilis cDNA showed that the recA gene was co-transcribed as an operon together with two upstream genes. Bioinformatic analysis revealed that the first ORF, BF638R1248, was a putative saccharopine dehydrogenase gene (sdh), encoding the SDH protein which may be involved in lysine degradation. The second ORF, BF638R1246/7 had homology to bcp genes, and encoded a putative Bactoferritin co-migratory protein (BCP) belonging to the thiol specific antioxidant superfamily. The functional roles of these proteins suggested that they might also be involved in survival after univalent electron stress. Quantitative RT-PCR showed that all three genes were transcriptionally regulated, but at different levels, after exposure to either metronidazole or H2O2. This suggests that in addition to being expressed as an operon, the genes may also possess independent regulatory elements. Functional characterisation of sdh and bcp was done using a gene mutation approach. Both insertional and deletion mutation methods were attempted but neither produced viable mutants in either of the upstream genes, suggesting that they may be critical for the survival of B. fragilis under normal growth conditions. The use of heterologous gene expression was subsequently employed to establish the functional role of the bcp gene and the encoded putative BCP. A similar approach for SDH was not successful. Heterologous complementation and protein expression of BCP in E. coli, with subsequent biochemical assay, showed that the B. fragilis bcp gene encoded a functional bacterioferritin co-migratory protein (BCP), which is a small thiol-specific protein with antioxidant properties. This BCP showed flexibility in its substrate preference with activity against H2O2, tet-butyl hydroperoxide and linoleic acid. The peroxidase activity of this TSA protein was dependent on the presence of one or more members of the thioredoxin group and NADPH. The BCP aided protection of the enzymatic activity of the B. fragilis redox sensitive Fe-S metalloenzyme Glutamine synthetase (GSIII) during exposure to 100 Î¼M H2O2. There was also evidence to suggest that it aided the recovery of the enzymatic activity of GSIII after exposure to 100 Î¼M H2O2. The findings of this research have resulted in the following hypothesis: The recA operon of B. fragilis acts during host invasion to contribute to the maintenance of DNA integrity and the anaerobic cellular environment until the oxyR regulated system and the pathogenicity genes are activated.